Daily Toothbrushing Frequency and the Association with Parental Report of Dental Pain and Discomfort in Preschool Children - Bruna Letícia Vessoni Menoncin; Patrícia Kochany Felipak; Fabian Calixto Fraiz; Juliana Feltrin de Souza; José Vitor Nogara Borges Menezes (Association of Support to Oral Health Research (APESB), 2022)
Objective: To evaluate the impact of daily toothbrushing frequency on parental reports of dental pain and discomfort in preschoolers. Material and Methods: An observational cross-sectional study was conducted involving 376 children between four and five years of age at public preschools in the city of Campo Magro, Brazil. Parents/guardians answered a socioeconomic questionnaire that contained a single question on the child's daily toothbrushing frequency and the Brazilian version of the Dental Discomfort Questionnaire (DDQ-B). Statistical analysis involved bivariate and multivariate Poisson regression analyses (α=0.05). Results: After the adjustments in the multivariate analysis, the prevalence of dental pain and discomfort was lower among children whose last visit to the dentist was for prevention (PR = 4.42; 95% CI: 1.75-11.14; p=0.002) and those with a higher daily toothbrushing frequency (PR = 2.13; 95% CI: 1.12-4.05; p=0.021). Conclusion: A lower toothbrushing frequency is associated with parental reports of dental pain and discomfort in preschoolers. Educational and preventive measures that stimulate an increase in daily toothbrushing frequency can contribute to a better oral health status in preschoolers, consequently, less prevalence of dental pain and discomfort.